2023
DOI: 10.3390/nu15112538
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Ex-Vivo Study of the Anti-Proliferative/Cytotoxic Bioactivity of Major Olive Secoiridoids’ Double Combinations and of Total Olive Oil Phenolic Extracts on Multiple Cell-Culture Based Cancer Models Highlights Synergistic Effects

Abstract: Several individual olive oil phenols (OOPs) and their secoiridoid derivatives have been shown to exert anti-proliferative and pro-apoptotic activity in treatments of human cancer cell lines originating from several tissues. This study evaluated the synergistic anti-proliferative/cytotoxic effects of five olive secoiridoid derivatives (oleocanthal, oleacein, oleuropein aglycone, ligstroside aglycone and oleomissional) in all possible double combinations and of total phenolic extracts (TPEs) on eleven human canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…OC is a monophenol belonging to the category of secoiridoids which has been largely investigated in terms of its anticancer activity [3]. Indeed, data obtained using different cancer cell lines have shown that it impinges on the number of cells by inhibiting proliferation and inducing apoptosis [4]. Similar observations have been reported in experimental models of liver, breast and lung cancer [5].…”
Section: Introductionmentioning
confidence: 69%
“…OC is a monophenol belonging to the category of secoiridoids which has been largely investigated in terms of its anticancer activity [3]. Indeed, data obtained using different cancer cell lines have shown that it impinges on the number of cells by inhibiting proliferation and inducing apoptosis [4]. Similar observations have been reported in experimental models of liver, breast and lung cancer [5].…”
Section: Introductionmentioning
confidence: 69%
“…Olive oil is widely recognized for its antioxidant properties but can also be used against cancer. Several studies have shown that oleuropein decreases cancer cell viability and exhibits pro-apoptotic effects through the p53-dependent pathway and by activating BAX and Bcl-2 genes in breast cancer cells (MCF-7) 123 . HT can also influence cell cycle progression by arresting cancer cells in the G0/G1 phase and reducing cyclin D1 levels.…”
Section: The Overall Polyphenols Anticancer Activities In Hncmentioning
confidence: 99%